Protozooplankton characterization of two contrasting sites in a tropical coastal ecosystem (Guanabara Bay, RJ) (Brazilian Journal of Oceanography, 2007)
Much time and resources have been invested in understanding plankton dynamics in Guanabara Bay (Brazil), but no attention has been devoted to the protozooplankton. To fulfill this lacuna, abundance and composition of protozooplankton were investigated from January to December - 2000 in fortnightly surface water samplings at two distinct water quality sites (Urca - closer to the bay entrance, more saline and cleaner waters; Ramos - inner reaches, hypereutrophic waters). The density at Urca (10³ - 10(5) cell.l-1) was one to three orders of magnitude lower than at Ramos (10(4) - 10(5) cell.l-1). A seasonal trend for nanoplankton and protozooplankton was more evident at Urca, but both sites had lower densities during the colder period. Small heterotrophic dinoflagellates (20-30 mm) were dominant in over 50% of the samples. The protozooplankton abundance and composition reflected the distinct trophic conditions states found at the bay. During the wet-warm season, non-oligotrich ciliates were representative of Ramos site with Gymnodiniaceae dinoflagellates, while tintinnids and heterotrophic dinoflagellates were predominantly found at Urca mainly during the dry-cold season. This first descriptive study towards the understanding of the intricate relationships among the microbial food web components reveals that protozooplankton can be a good indicator of water quality conditions at the bay.